Let's address each question step by step:
Question 1:
- Correct simplification of \( \frac{1000^2}{3} \): \[ 1000 = 10^3 \] \[ 1000^{2/3} = (10^3)^{2/3} = 10^{3 \cdot \frac{2}{3}} = 10^2 = 100 \] Kali is correct.
Question 2:
- Simplify \( 243^{3/5} \): \[ 243 = 3^5 \quad (\text{since } 3^5 = 243) \] \[ 243^{3/5} = (3^5)^{3/5} = 3^{(5 \cdot \frac{3}{5})} = 3^3 = 27 \] So, \( 243^{3/5} = 27 \).
Question 3:
- Write the radical form of the expression \( 25^{1/4} \): \[ 25^{1/4} = \sqrt[4]{25} \]
Question 4:
- Simplest form of \( 25^{1/2} \): \[ 25^{1/2} = \sqrt{25} = 5 \]
Question 5:
- Rewrite the expression \( 27^{1/2} \cdot 27^{1/4} \): \[ 27^{1/2} \cdot 27^{1/4} = 27^{1/2 + 1/4} = 27^{2/4 + 1/4} = 27^{3/4} \]
Question 6:
- Equivalent expression for \( -\left(b^{1/4}\right)^{12} \): \[ -\left(b^{1/4}\right)^{12} = -b^{(1/4) \cdot 12} = -b^3 \] Therefore, the answer is: −b^3.
Question 7:
- Find the value of \( x \) in \( -x^{3/2} = -27 \): Divide both sides by -1: \[ x^{3/2} = 27 \] To solve for \( x \), raise both sides to the power of \( \frac{2}{3} \): \[ x = 27^{\frac{2}{3}} = (3^3)^{\frac{2}{3}} = 3^2 = 9 \] Hence, \( x = 9 \).
Question 8:
- Solve for \( x \) in \( 27x^{3/4} - 1 = 26 \): \[ 27x^{3/4} = 27 \] Divide by 27: \[ x^{3/4} = 1 \] Raise both sides to \( \frac{4}{3} \): \[ x = 1^{\frac{4}{3}} = 1 \]
Question 9:
- Using exponent properties, which is equivalent to \( (2^{-\frac{1}{2}})^3 \cdot 2^{-\frac{1}{2}} \): \[ 2^{-\frac{3}{2}} \cdot 2^{-\frac{1}{2}} = 2^{-\frac{3}{2} - \frac{1}{2}} = 2^{-2} = \frac{1}{4} \]
Question 10:
- Find the equivalent expression for \( \frac{\sqrt{216}}{27^{1/3}} \): First simplify each part.
- \( \sqrt{216} = \sqrt{36 \cdot 6} = 6\sqrt{6} \)
- \( 27^{1/3} = 3 \)
Thus, \[ \frac{6\sqrt{6}}{3} = 2\sqrt{6} \]
Question 11:
- For the equation \( (8^{-\sqrt{4}})^{-24} \cdot (8^{-\sqrt{3}})^{16} = 8^{-48} \):
- Notice that both terms on the left should use multiplication of exponents, leading to:
- The equation is false because the exponents should be added rather than multiplied.
Question 12:
- Simplify \( 7^{-4} \cdot 7^{3}/\sqrt{49} \): \[ \sqrt{49} = 7 \quad \text{so} \quad \frac{7^{3}}{7} = 7^{2} \] Then, \[ 7^{-4} \cdot 7^{2} = 7^{-4 + 2} = 7^{-2} = \frac{1}{7^{2}} = \frac{1}{49} \]
Summary of Answers:
- Kali
- \( 27 \)
- \( \sqrt[4]{25} \)
- \( 5 \)
- \( \frac{3}{4} \)
- −b^3
- \( 9 \)
- \( 1 \)
- \( 2^{-2} \) (or \( \frac{1}{4} \))
- \( 2\sqrt{6} \)
- The equation is false because the exponents should be added rather than multiplied.
- \( \frac{1}{49} \)